A Functional SNP Catalog of Overlapping miRNA‐Binding Sites in Genes Implicated in Prion Disease and Other Neurodegenerative Disorders. Issue 10 (18th August 2014) - Saba, Reuben; Medina, Sarah J.; Booth, Stephanie A.
<x xml:space="preserve">Abstract</x> We identified numerous SNPs overlapping miRNA‐binding sites within an assortment of genes implicated in the very early mechanisms of neurodegeneration characterized by Prion disease. Many of these SNPs are functional as they alter the binding potential of spatiotemporally coexpressed miRNAs. Additionally, we also show that these SNPs are common within the human population. Taken together, our data contribute to the emerging awareness that miRNAs and associated SNPs could account for detrimental neurological states that afflict humans. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>